2008
DOI: 10.3758/pbr.15.3.615
|View full text |Cite
|
Sign up to set email alerts
|

Locating attractiveness in the face space: Faces are more attractive when closer to their group prototype

Abstract: Previous research on faces has shown a relation between facial attractiveness and the mathematical averageness of a face (e.g., Langlois & Roggman, 1990). Rhodes, Harwood, Yoshikawa, Nishitani, and McLean (2002) also showed that people from different social groups (e.g., Caucasian and Asian) show high intergroup correlations in attractiveness ratings of the same mathematically average faces, regardless of the group memberships of the raters or of the faces being rated. Yet, relatively little is known about how… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 27 publications
2
30
0
Order By: Relevance
“…Furthermore, typical faces are judged more attractive than distinctive faces3233, and a meta-analysis has shown that the appeal of averageness is not restricted to face race or sex34, although it might be linked with visual experience35.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, typical faces are judged more attractive than distinctive faces3233, and a meta-analysis has shown that the appeal of averageness is not restricted to face race or sex34, although it might be linked with visual experience35.…”
Section: Introductionmentioning
confidence: 99%
“…The other shifts are in the direction that discriminates humans from ancestral hominids, and aesthetic preferences lying along the ancestral-to-derived discriminant have been documented in both the face and the body (Magro, 1997(Magro, , 1999. This brings us to the interpretation of the literature that documents a shift toward European norms in attractive nonEuropean faces and is, therefore, discordant with Potter and Corneille (2008). A convenient explanation is the economic domination of Western societies and the strong global presence of Western culture.…”
Section: Methodological Issuesmentioning
confidence: 83%
“…However, Rhodes et al (2005) could not do this and, hence, did not address the extent to which the higher attractiveness of Eurasian faces resulted from variation along the discriminant distinguishing European from Asian faces, rather than from other shape components. Potter and Corneille (2008) used the "rand lock" feature in FaceGen, which keeps dimensions that are key to a group constant, to generate random faces for each population. It is questionable how well FaceGen achieves this.…”
Section: Methodological Issuesmentioning
confidence: 99%
See 1 more Smart Citation
“…Moving a facial image closer to the average increases its attractiveness (Langlois and Roggman 1990). This "beauty-in-averageness effect" only works, however, when the features of the faces are average of the group to which a face belongs (Potter and Corneille 2008).…”
Section: Cognition Categorisation and Prototypementioning
confidence: 99%